Total Mortality by Elevated Transferrin Saturation in Patients With Diabetes - Ellervik, Christina (American Diabetes Association, 2013)
OBJECTIVE: It is not known to what extent iron overload predicts prognosis in patients with diabetes after diagnosis or whether iron overload is a risk factor independent of the HFE genotype. We investigated total and cause-specific mortality according to increased transferrin saturation (≥50 vs. <50%), whether mortality is driven by the HFE genotype, and whether early measurement of transferrin saturation helps to predict mortality outcome. RESEARCH DESIGN AND METHODS: Cohort 1 included patients with late-onset type 1 diabetes (n = 716) with a cross-sectional measurement of transferrin saturation and HFE genotype. Cohort 2 included consecutively recruited patients with any diabetes (n = 6,120), transferrin saturation measurement at referral, and HFE genotype if transferrin saturation was above 50%. RESULTS: In cohort 1, the hazard ratio for total mortality was 2.3 (95% CI 1.3–3.9; P = 0.002) and for cause-specific mortality by neoplasms was 5.8 (2.4–14; P = 0.00007) in patients with transferrin saturation ≥50 vs. <50%. Excluding genotypes C282Y/C282Y and C282Y/H63D gave similar results. The hazard ratio for total mortality was 4.0 (1.2–13; P = 0.01) and for cause-specific mortality by neoplasms was 13 (3.6–49; P = 0.0001) in patients with C282Y/C282Y versus wild type. In cohort 2, total mortality was not different in patients with transferrin saturation ≥50 vs. <50%. In patients with late-onset type 1 diabetes and transferrin saturation ≥50%, the hazard ratio for total mortality was 0.4 (0.2–0.9; P = 0.03) in cohort 2 versus cohort 1. CONCLUSIONS: Increased transferrin saturation and HFE genotype C282Y/C282Y predict total mortality in patients with late-onset type 1 diabetes, and increased transferrin saturation after diagnosis is an independent risk factor. Early measurement of transferrin saturation in these patients leading to early intervention improves life expectancy.